Assessment of the correlation between residual hearing and audiologic outcomes after cochlear implantation in patients with cochlear nerve deficiency. Issue 5 (19th August 2022) - Lu, Simeng; Wei, Xingmei; Kong, Ying; Chen, Biao; Chen, Jingyuan; Zhang, Lifang; Yang, Mengge; Liu, Sha; Li, Yongxin
Abstract: Objective: This study aimed to assess the correlation between residual hearing and audiologic outcomes after cochlear implant (CI) surgery in patients with cochlear nerve deficiency (CND). Methods: This retrospective study included 57 patients with CND who underwent CI surgery. Patients were divided into four groups according to hearing level (80–95, 95–110, 110–120, and >120 dB) and three groups according to residual hearing (entire spectrum hearing, partial spectrum hearing, and no spectrum hearing) based on the measured response at each frequency. Auditory performance (categorical auditory performance [CAP], Infant–Toddler Meaningful Auditory Integration Scale [IT‐MAIS]) and speech perception (speech intelligibility rating [SIR] and meaningful use of speech scale [MUSS]) were assessed before and 2 years after the surgery. Results: Forty‐seven (82.5%) patients had complete or total hearing loss (≥95 dB) and 17 (29.8%) had no spectrum hearing before CI surgery. Twenty‐nine (50.9%) patients did not exhibit residual hearing at 4 kHz. All patients demonstrated an improvement in auditory performance and speech perception: the CAP score in the 80–95 dB group was significantly higher than that in the 110–120 and >120 dB groups, and the entire spectrum hearing group showed significantly higher CAP, SIR, and IT‐MAIS scores than the partial spectrum hearing group and significantly higher CAP, SIR, IT‐MAIS, and MUSS scores than the no spectrum hearing group. Conclusion: For patients with CND, residual hearing, especially high‐frequency residual hearing, was poor and postoperative audiologic outcomes were significantly associated with the range of residual hearing. Level of Evidence: 4